Does the Time of Radiotherapy Affect Treatment Outcomes? A Review of the Literature. Issue 4 (April 2017) - Chan, S.; Rowbottom, L.; McDonald, R.; Bjarnason, G.A.; Tsao, M.; Danjoux, C.; Barnes, E.; Popovic, M.; Lam, H.; DeAngelis, C.; Chow, E.
Abstract: Circadian rhythm-dependent cell cycle progression produces daily variations in radiosensitivity. This literature review aims to summarise the data on whether radiotherapy outcomes differ depending on administration time. A literature search was conducted on Ovid Medline, Embase, Cochrane Central Register of Controlled Trials and PubMed using key words such as 'radiotherapy', 'circadian rhythm', 'treatment outcome' and 'survival'. Articles evaluating the correlation between radiotherapy time and outcomes in cancer patients were included and relevant information was extracted. Nine studies met the inclusion criteria. Four investigated lung cancer patients undergoing stereotactic radiosurgery for brain metastases, with one study observing improved local control and survival in patients treated in the morning. Another two studies with breast and cervical cancer patients observed that the prevalence of toxicities was higher in afternoon and morning cohorts, respectively. Two studies in head and neck cancer patients found trends indicating morning patients experienced less oral mucositis. Increased toxicities and biochemical failure rates were associated with evening treatment in prostate cancer patients. As inconsistencies in the literature exist regarding the time dependency of radiotherapy outcomes, further investigation is warranted. Highlights: Circadian rhythm dependent cell cycle progression produces daily variations in radiosensitivity. Nine studies have been conducted to determine whether time of radiotherapy administration affects treatment outcomes in cancer patients. Inconsistencies in the literature exist regarding the time-dependency of radiotherapy outcomes. More pre-clinical studies are necessary to characterize the effect of circadian rhythms and radiotherapy on cell cycle progression to improve chronotherapy study methodologies.